ASURANSI SYARIAH SEBAGAI INSTRUMEN PERLINDUNGAN FINANSIAL MASYARAKAT BERPENGHASILAN RENDAH - Desi Devrika Devra (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study examines the role of sharia insurance as a financial protection instrument for low-income people in Indonesia. Using a descriptive qualitative approach based on literature study, this study analyzes the challenges, as well as opportunities for the development of inclusive sharia insurance. The results of the study show that sharia insurance has great potential to become an instrument of financial protection for low-income people through the principles of tabarru', ta'awun, and fair profit sharing. However, the low level of Islamic financial literacy and the Islamic financial inclusion index based on the 2024 National Survey on Financial Literacy and Inclusion are the main obstacles. The strategy of expanding access through digitalization, sharia insurance products, and inter-institutional cooperation is identified as a solution to encourage the development of sharia insurance to low-income segments of society. Keywords: Islamic Insurance, Financial Protection, Low-Income Communities, Financial Inclusion, Takaful